3/х-3 + 3/х в квадрате - 7х+12=1-х/х-4

3/х-3 + 3/х в квадрате - 7х+12=1-х/х-4
Гость
Ответ(ы) на вопрос:
Гость
 3   +      3       = 1-x x-3    x²-7x+12     x-4 Разложим на множители: x²-7x+12=0 D=49-48=1 x₁=7-1=3        2 x₂=7+1=4        2 x²-7x+12=(x-3)(x-4)     3   +      3      -    1-x  =0 x-3      (x-3)(x-4)     x-4 x≠3     x≠4≠ 3(x-4)+3-(1-x)(x-3)=0 3x-12+3-(x-x²-3+3x)=0 3x-9+x²-4x+3=0 x²-x-6=0 D=1+24=25 x₁=1-5=-2        2 x₂=1+5=3 - не подходит, так как х≠3        2 Ответ: -2.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы